PSYCHOSOCIAL SUPPORT IN SELF-ACTUALIZING MAYER ROKITANSKY KUSTER HAUSER SYNDROME WOMEN - Gardha Rias Arsy; Retty Ratnawati (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2021)
Background: Self-concept is an individual's mode to completely see his personality, dealing with intelligence, emotion, spirituality, physical form, or social form. It provides continuity, consistency, and completeness for an individual. An individual with excellent self-concept could maintain their feeling of stability and positive behaviors directed for himself or other people. From the data of the MRKH community, thirty-three people were suffering MRKH in Indonesia. Objectives: This research explored the self-concept experiences of women with Mayer Rokitansky Kuster Hauser syndrome. Methods: This research is qualitative research with a phenomenological approach Interpretation. The data were collected from an in-depth interview with a structured design for seven participants. Results: Such reproduction organ problems influence their life qualities because they think that a perfect woman's identity is to have a normal reproduction organ. This problem also influences their psychologies and have psychological and emotional traumas as well as self-concept changes. However, they tried to endure it and actualize themselves because they obtained support from their families and the MRKH community. Conclusion: The states suffered by women with reproduction system problems influenced their psychological stabilities. The participants' medical teams should collaborate with psychiatrists and psychologists to foster a positive self-concept of the participants. Psychological counseling could improve their self-confidence and foster positive self-concepts.